Under the Skies of Olympus: Three Types of Divine Landscapes in the Homeric Hymns - Vasiliauskaitė, Vaiva (Literatūra, 2023)
The paper discusses the landscapes of Apollo, Hermes, Pan, and Demeter in the Homeric hymns, analysing how particular landscape representations articulate the gods’ functions and identities, their relationship to humanity and the structure of the Olympic cosmos. It is argued that an in-depth examination of the representation of landscape in Ancient literature reveals patterns of representation that contribute to a deeper understanding of the religious worldview of the ancient Greeks.
Keywords: Homeric Hymns; Hymn to Apollo; cosmography; Olympic cosmos; sacred landscapes